Catfish market development strategy. Issue 1 (October 2021) - Wahid, A; Gosari, B A J; Firman; Cangara, A S
Abstract: Market development is one important aspect in business activities. The market has a strategic value as a meeting place for sellers and buyers. A number of small culinary businesses have sprung up by providing creative products made from catfish. Therefore the companies producing catfish need to develop their marketing strategy as part of running their businesses. This research was conducted in the Gowa (Juku Lele Cooperative) and Makassar regions. Research is needed that can answer some questions about developing catfish business. The purpose of this study was to determine market development strategies for a catfish producing business, starting with self-evaluation including internal and external evaluations. Primary data is obtained through direct interviews with administrators, members and employees of the Juku Lele Cooperative, collector, seller and end consumer with samples : 24 members and 51 non-members who had catfish floating cages as producer, one person as collector, 3 people as seller, 25 people as end consumer. One of the success factors in developing business marketing strategies is to have products that are in accordance with the wishes of consumers.There were two forms of marketing channels. They were direct and indirect selling. The value of marketing efficiency for marketing channel I of 0% and 2 of 1, 57%. This means that marketing channel I is more efficient than marketing channel II. On marketing channel I the marketing margin is Rp. 0 with Ski is 100%, while the marketing channel II involving one marketing agency with a marketing margin of Rp. 4.000.00 with Ski is 80%. This matter shows that short marketing channels are more efficient than marketing channels the long one, but in fact, marketing channel II is more dominant because it involves a lot of people, resources and capital. Analysis of market development strategies starting internal where more effective for marketing margin is Rp. 0, this is an ideal condition. in fact, external more dominant.